SISTEM ARSIP SURAT MASUK DAN KELUAR DI BADAN KESATUAN BANGSA DAN POLITIK BANYUWANGI - Johan Dika Pratama; Akhlis munazilin (JOURNAL SAINS STUDENT RESEARCH, 2026)
Rapid technological development in the era of globalization has significantly influenced all aspects of organizational activities, including administrative management. This study aims to design and implement a web-based information system for managing incoming and outgoing mail to improve efficiency and accuracy in document handling at a governmental institution. The research method used is a descriptive method with a system development approach, including data collection through observation, interviews, and documentation, followed by system analysis, design, implementation, and testing. The results show that the proposed web-based mail archive information system is able to facilitate faster data processing, improve document tracking, reduce the risk of data loss, and support more systematic and efficient administrative services. The system also enhances flexibility in accessing mail data and supports better decision-making processes within the organization.